2021
DOI: 10.3389/fonc.2021.639644
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Blood Markers in Primary Central Nervous System Lymphoma Patients Treated With High-Dose Methotrexate-Based Therapy

Abstract: Purpose: Primary central nervous system lymphoma (PCNSL) is a rare type of extra-nodal non-Hodgkin lymphoma, but the prognostic value of blood parameters indicating systemic inflammation and nutritional status remains unknown. We aim to explore the prognostic role of blood parameters in PCNSL.Methods: All PCNSL patients diagnosed at West China Hospital between February 2011 and February 2020 were retrospectively screened. For patients who were initially treated with high-dose methotrexate (HD-MTX)-based therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…Here, we demonstrated the same trend in a pure PCNSL cohort. This was in keeping with several studies by other author groups [ 1 , 2 , 21 ]. In the Jung et al study [ 1 ], NLR greater or equal to 2.0 was associated with worse survival; of note, we also arrived at the same cut-off value of 2.0 for our baseline NLR, with effect estimates in the same direction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, we demonstrated the same trend in a pure PCNSL cohort. This was in keeping with several studies by other author groups [ 1 , 2 , 21 ]. In the Jung et al study [ 1 ], NLR greater or equal to 2.0 was associated with worse survival; of note, we also arrived at the same cut-off value of 2.0 for our baseline NLR, with effect estimates in the same direction.…”
Section: Discussionsupporting
confidence: 92%
“…In the Jung et al study [ 1 ], NLR greater or equal to 2.0 was associated with worse survival; of note, we also arrived at the same cut-off value of 2.0 for our baseline NLR, with effect estimates in the same direction. Similarly, in a more recent Luo et al study [ 21 ], the group found that NLR > 1.79 correlated with worse PFS.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, there are very limited data about the validity of these scoring systems in the context of rrPCNSL. Notably, all existing prognostic models are based on clinical parameters measured at baseline; no robust data are yet available on dynamic factors measured during therapy and/or based on clinical, pathobiological or imaging characteristics of PCNSL ( 33 36 ). Identifying those most at risk of being refractory or relapse in PCNSL is further complicated by different first line regimens being employed in routine clinical practice ( 33 ).…”
Section: Predicting the Risk Of Relapse In Pcnslmentioning
confidence: 99%
“…Lymphocytes play crucial roles in tumor defense by inducing cytotoxic cell death 14 . Therefore, SII has been reported to predict the outcomes in patients with PCNSL 15,16 and DLBCL [17][18][19] . However, the sample size is quite limited due to the relatively low incidence and stern discipline of diagnosis.…”
Section: Introductionmentioning
confidence: 99%